Right atrial pressure alterations during echocardiography-guided-catheterization predict tricuspid valvular impairment: a novel method for the creation of a rabbit model of Staphylococcus aureus endocarditis - Wang, Mei-lian (BioMed Central, 2014)
BACKGROUND: We previously reported the use of a catheter system to damage the tricuspid valve and create infectious endocarditis (IE) in an animal model. The current study aims to create a faint IE model suitable for antibiotic prophylaxis using a low bacterial inoculum. We also aim to explore a way to quantitatively assess valvular impairment and to predict the success of the IE models during catheterization. METHODS: Ninety rabbits were assigned to two groups according to the density of bacteria inoculated (1 × 10(5) CFU for Group A and 1 × 10(4) CFU for Group B). A catheter system consisting of a polyethylene catheter and a guide wire were used to damage the valve. The catheter system was passed through the rabbits’ tricuspid valves under echocardiographic guidance. A pressure transducer was used to assess right atrial pressure (P(RA)) before and just after valvular damage to calculate the pressure alterations (ΔP(RA)). The animals in group A and B were divided into 3 subgroups according to the ΔP(RA) (0–5 mmHg for Groups A(1) and B(1); 5–10 mmHg for Groups A(2) and B(2); 10–15 mmHg for Groups A(3) and B(3)). Staphylococcus aureus (ATCC 29213) inoculation was performed 24 hr after cardiac catheterization. RESULTS: Faint IE was confirmed in 20%, 93.3%, 26.7%, 6.7%, 20%, and 33.3% of the rabbits in Groups A(1), A(2), A(3), B(1), B(2), and B(3), respectively. There was no difference in the LV/RV ratio and V(TR) of the No-IE, faint-IE, and severe IE animals. Faint IE rabbits had a larger ΔP(RA) than No-IE rabbits (7.81 ± 1.21 vs. 2.48 ± 1.0, P < 0.01, for Group A; 7.60 ± 1.32 vs. 2.98 ± 1.08, P < 0.01, for Group B). The ΔP(RA) of severe IE and faint IE rabbits was significantly different (13.11 ± 1.31 vs. 7.81 ± 1.21, P < 0.01, for Group A; 12.73 ± 1.44 vs.7.60 ± 1.32, P < 0.01, for Group B). CONCLUSION: ΔP(RA) could be used to assess valvular impairment. Controlling the value of ΔP(RA) during catheterization and inoculating of an appropriate dose of bacteria was associated with a successful IE model.